Association of Nuclear VDR Immunoexpression with Breslow’s Thickness in Acral Melanoma - Sholihah, Fitria; Usman, Hermin Aminah; Dewayani, Birgitta Maria (Althea Medical Journal, 2023)
Background: Acral melanoma (AM) is a subtype of malignant melanoma (MM) that has a predilection for glabrous skin and is the most common type of melanoma among Asians. Depth of invasion is one of the prognostic factors in AM. VDR may have an association with depth of invasion in AM. However, reports from Asian patients are still lacking. The aim of this study was to explore the association between VDR immunoexpression and depth of invasion in AM patients in Bandung, Indonesia.Methods: This study was a retrospective cross-sectional study that analyzed the nuclear and cytoplasm VDR expression of melanoma cells and its association with Breslow’s thickness in patients with AM in Dr. Hasan Sadikin General Hospital Bandung. VDR immunostaining was performed on paraffin blocks. The Breslow thickness was measured using dot slide software. Chi square statistical analysis was done to determine the results.Results: Of the 30 patients, 73% had a Breslow thickness of >4 mm.  There was a significant inverse association between nuclear VDR immunoexpression and Breslow thickness of AM (p<0.001), but not for cytoplasmic VDR immunoexpression (p=0.914). Conclusion: Low nuclear VDR immunoexpression is associated with the depth of invasion in AM. Nuclear VDR immunoexpression possibly affect progression and should be considered before administration of vitamin D therapy in AM.